DEVELOPMENT OF PLAYING SKILLS SEPAK TAKRAW EXERCISES MODELS BASED ON INTERACTIVE MULTIMEDIA - Didik Purwanto (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
AbstractThe purpose of this research and development are to developing playing skills sepak takraw exercises models. This research begins with needs analysis using survey method and then developing learning resources with corresponding characteristic with the needs analysis result. The development of playing skills sepak takraw exercises models based on interactive multimedia package in print media form and soft file *exe package in VCD forms. The research method using research method and the development with developing steps design by Borg and Gail. Surely, that method is modifying by the researcher to corresponding with the researcher requirement. The subject of this research is 35 university students who joined Unit Kegiatan Mahasiswa or the student activities unit sepak takraw at Tadulako University. Small group test result obtained percentage of 91,69% with good category, while the result of large group test obtained percentage 94,16% with good category, and from exercise data according to the sepak takraw couch this product can be used in the real exercise. Based on effectiveness test result, empirically proven that the product result playing skills sepak takraw exercises models based on interactive multimedia has effectiveness which very good.Key Word : Development, Sepak Takraw Exercises Models, Interactive Multimedia.